2019
DOI: 10.1111/jocd.13109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of allogenic human Wharton's jelly stem cells seeded onto acellular dermal matrix in healing of rat burn wounds

Abstract: Background Various methods were introduced to overcome the autograft shortage in burn wound care, including cell transplantation and tissue engineering. Aims To evaluate the healing effect of allogenic human Wharton's jelly stem cells (hWJSCs) seeded onto acellular dermal matrix (ADM) in rat burn injuries. Patients and Methods Human Wharton's jelly stem cells provided from umbilical cord tissue were characterized before transplantation, and the growth kinetic was determined. Skin samples from cosmetic surgerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…23 hAFSCs isolated in our study from different age groups of pregnant mothers were positive for CD73, CD90, and CD105 as mesenchymal markers and negative for CD34 and CD45 as hematopoietic markers, confirming the abovementioned studies. 14,15,[20][21][22][23][24] hAFSCs have been shown to have self-renewal ability and a high growth rate, making them a good candidate for cell transplantation. 25 Varghese et al, in a systematic review on 41 articles regarding factors affecting adipose tissue stem cell viability and function, demonstrated a decreased proliferation and differentiation potential of adipose tissuederived stem cells (AdSCs) with an increase in age.…”
Section: Discussionmentioning
confidence: 99%
“…23 hAFSCs isolated in our study from different age groups of pregnant mothers were positive for CD73, CD90, and CD105 as mesenchymal markers and negative for CD34 and CD45 as hematopoietic markers, confirming the abovementioned studies. 14,15,[20][21][22][23][24] hAFSCs have been shown to have self-renewal ability and a high growth rate, making them a good candidate for cell transplantation. 25 Varghese et al, in a systematic review on 41 articles regarding factors affecting adipose tissue stem cell viability and function, demonstrated a decreased proliferation and differentiation potential of adipose tissuederived stem cells (AdSCs) with an increase in age.…”
Section: Discussionmentioning
confidence: 99%
“…At preclinical level, five studies [one CT (Pourfath et al, 2018) and four TE strategies (Steffens et al, 2017;Kaita et al, 2019;Mahmood et al, 2019;Nazempour et al, 2020)] have evaluated the use of hMSCs for burn injuries in the last 5 years ( Table 3).…”
Section: Preclinical In Vivo Studiesmentioning
confidence: 99%
“…In this case, each of the four studies reported, used a different hMSCs population (Table 3): deciduous teeth (hDT-MSCs) (Steffens et al, 2017), hUCB-MSCs (Mahmood et al, 2019), hAT-MSCs (Kaita et al, 2019) and hWJ-MSCs (Nazempour et al, 2020). The average follow-up of these studies was 15.5 ± 5.9 days and third-degree burns in mice and rats was the preferred model, although the type of TESS evaluated varied.…”
Section: Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…They express cell surface markers such as CD44, CD73, CD90, and CD105, and lack the expression of hematopoietic markers such as CD34 and CD45 [21]. They have been isolated from various sources such as bone marrow (BM) [22], adipose tissue [23], and umbilical cord Wharton's jelly [24]. MSCs have therapeutic effects in various inflammatory diseases due to its hypoimmunogenic and immunoregulatory properties and can be the home to the site of injury, limit inflammation through cytokine release, stimulate healing through growth factor expression, alter host immune responses through secretion of immune-modulatory proteins, and secrete anti-apoptotic factors [25].…”
Section: The Characteristics Of Mscs As Emerging Therapy Of Ucmentioning
confidence: 99%